IMPLEMENTATION CHALLENGES OF THE INDEPENDENT CURRICULUM: A QUALITATIVE STUDY AT MTS INSAN MADANI, SITUBONDO - Kulsum, Ummi; Sundarwati, Desi; Sihinda, Vita Nur; Jannah, Nafisah Mafazatul; Puspitasari, Yesi (Journal on Research and Review of Educational Innovation, 2024)
A curriculum is a plan and regulation containing objectives, content, learning materials, and teaching methods used as guidelines in teaching and learning activities. The curriculum is the leading guide for educators to ensure every student has access to rigorous academic experiences. The word "Curriculum" comes from the Latin Currece, which means "Running" or "Continuing". The curriculum can also be interpreted as a set or system of plans and arrangements regarding learning materials that can be used as teaching and learning activity guidelines. In essence, the curriculum can also be called a learning plan. Therefore, all parties involved and directly related to the function of this curriculum must understand it. This research is qualitative. The method used is the systematic literature review (SLR) approach, which collects data and evaluates and synthesizes relevant evidence. The target of this study was students at the Mts. Insan Madani educational unit is located in Gebang Village, Jatibanteng District, Situbondo Regency. The data collection technique used is qualitative data that is reviewed and collected in the form of writing and images; qualitative data can be obtained through various data collection techniques, such as images, voice recordings, and videos. Implementing the independent curriculum is a practical learning experience and is easy to communicate with various parties. The results of this study reveal that implementing the independent curriculum at the educational unit level has several influences, namely from its natural resources and the changes in the existing curriculum. As a result, some teachers still do not understand how to implement the independent curriculum.